PENGARUH PENGGUNAAN TIGA MEREK OLI TERHADAP TEMPERATUR MESIN DAN KONSUMSI BAHAN BAKAR PADA MOTOR HONDA PGM-FI REVO FIT 110 CC - Wara Wangge, Gusti F. X; Viva Servianus, Yohanes; Pereira Maia Pinto, Gaspar; Rompi, Rofinus (Blueprint Journal, 2025)
This research analyzes the effect of three oil brands, namely MPX1, Federal Ultratec, and Enduro 4T on engine operating temperature and fuel consumption on the Honda Revo Fit 110 cc PGM-FI motorbike. The test was carried out at an engine speed of 17,000 rpm for 30 minutes using Pertalite fuel. The parameters observed include engine temperature and remaining fuel volume. The results show that the type of oil influences thermal performance and fuel efficiency. MPX1 oil produces the highest temperature of 111°C with the most economical fuel consumption (968 ml remaining). The Federal Ultratec showed a temperature of 109°C with 900 ml remaining, while the Enduro 4T had a low of 107°C with 880 ml remaining. MPX1 with the semi-synthetic SAE 10W-30 formulation has better viscosity stability than the other two mineral oils, so it is able to maintain combustion efficiency and engine performance. Overall, the MPX1 provides the most optimal performance, the Federal Ultratec excels in engine protection at high loads, and the Enduro 4T is better in lowering operating temperatures. Choosing oil that matches engine specifications is an important factor in maintaining fuel efficiency and engine durability.